Analysis of excessive sheath currents in multiple cable circuits bonded to the same grounding grid - Gen Li; Wenjun Zhou; Chengke Zhou; Hang Wang; Chen Pan (High Voltage, 2025)
Abstract In urban power networks, a common practice is to bond numerous high‐voltage cable circuits to a single grounding grid located in underground tunnels, primarily for reasons of installation convenience. In these situations, excessively high levels of sheath currents were often detected during routine inspections, but no electrical faults were found to be responsible. Previous publications ignored the currents flowing through the shared grounding points into the closed sheath loops of different circuits. In this paper, a mathematical model is established for the current circulating among sheath loops of different circuits, and the factors influencing the circulating current were analysed. The abnormal excessive sheath current is demonstrated to be an increase in the circulating current due to the combined effect of electromagnetic coupling and the shared grounding grid. The circulating current depends on the induced voltages which, in turn, depends on the cable layouts and load currents. The effects of these factors are evaluated in various scenarios. The increase of the circulating current is verified in a field case where four electrically healthy cable circuits sharing the same grounding points were found to have abnormal excessive sheath currents.